Lived Experiences of Home-Based Computer Technicians - Canque, Marvin S.; Trinidad, Lloyd Matthew Derasin,Glenn A.; Pajaron Jr., Gregorio P. (The journal of contemporary issues in business and government, 2021)
The study focuses on the lived experiences of an on-call computer technicianwhose place of work is at home but accept home services and the study used the phenomenological research design method. There were seven (7) male informants in the study and they are selected based on data saturation method. The main research instrument of the study is the researcher using interview method. Moreover, the analysis was donethrough detailed reading, rereading and interpretation of the transcripts and identified initial themes or codes, defining, redefining of codes and modifying of codes through association, contrasting and formulation of themes. The results revealed eight major themes including“Flexible Working Hours”, “Accessible working place”, “Financial/Economic needs matter”, “Experiencing Clients Lack of Trust and Confidence”, “No co-workers to ask for help”, “Inadequate tools and Kits used for servicing”, “Hunting for an alternative source of income”, and “What Matters is Doing the Job You Love”. It is Recommended that home service computer technicians should undergo seminars and training-workshops on the new trends and updates of the computer both software and hardware. In addition, retraining and practices to the new tools and equipment’s configure latest computer security protection software’s could be a great foundation to strengthen the technician’s knowledge and ability. Moreover, computer technicians should establish application software/online platform wherein the customer would visit the application software and apply for a service they needed.